Laser Doppler sensor of the angular speed of rotation of a disc with a retroreflective surface - Dolya, Gregory; Bondarenko, Kostiantyn (European Journal of Applied Sciences, 2021)
A method for measuring angular speed of rotation of a disc is considered, taking into account features of retroreflecting surface based on micro glass beads. Method involves single-beam object probing, detection of scattered radiation and spectral analysis of the recorded photocurrent. A mathematical model of the proposed method is described. Results of physical simulation are presented in form of plots, showing dependencies of received signals Doppler shift on the frequency of rotation. Analysis of changes in registered photocurrent was done, taking into account changes due to the vary of the angular velocity of the disc rotation, the angle of inclination of the disc surface to the incident beam, the beam diameter, and the position of the illuminated spot on the disc.